Development of an augmented reality based facility layout planning and optimization / Tan Chee Hau - Tan , Chee Hau (2020)
This study presents an augmented reality (AR) based facility layout planning (FLP) system with an optimization algorithm to assist facility layout designers in decision making. AR is a technology that blends virtual data such as 3 Dimensional (3D) model into the actual world. FLP is about the allocation of facilities to achieve smooth, efficient and effective processes. FLP’s research can be divided into the procedural approach, algorithmic approach, Virtual Reality (VR) and AR-based approaches. AR-based FLP effectively addressed the traditional FLP issues such as facilitating the addition of a new machine in an existing production floor, rearrangement of machines’ sequence, etc. The advantages of AR-based FLP approach over the other approaches are the shorter time taken to build its model and its flexibility in the design modification. Previous studies in AR and FLP had shown that the digitalization of existing objects is needed. The simple plane, blocks and cylinders are used to overlay onto the actual objects as representation in this research. An AR assisted FLP software was built with 4 modules to locate a new machine in an existing layout, to utilize a space given and optimize a production schedule, to locate a shared facility in an existing layout and to optimize a loop layout robotic cell process. The space occupied and the parts’ travelled distance are compared to support in decision making. Production line commonly used algorithm such as shortest processing time (SPT), longest processing time (LPT), cycle time optimization and centre of gravity (CoG) algorithm are coded in this system which enables the production schedule and sequence to be optimized. Four cases studies have investigated this research whereby case study-1 is to evaluate the most suitable position and orientation of a new machine to be placed in an existing production floor, case study-2 is to maximize the area given and further maximize the productivity by optimizing the production sequence, case study-3 is about identifying the best position of a shared facility whereas the case study-4 identified the most effective production sequence in a robotic conveyor cell. The developed AR-based FLP software allows users to re-configure the suggested layout by moving the facilities in the AR environment and the results are reflected in real-time. This research is useful for production line which requires flexibility and agility. The developed AR-based FLP software is fast and effective.